Facing the Abyss: Ontological Distance in the Poetry of a Carthusian Monk - Hujanen, Riitta ca. 20./21. Jahrhundert (Teresianum, 2025)
‘Facing the Abyss’ refers to the liminal and temporal theme of ‘Ontological Distance’ in the poetry of an anonymous Carthusian monk in the period 1964-2024. This article approaches the topic mainly from the perspectives of Catholic monastic spirituality and the Carthusian tradition. The thematic analysis of the selected texts explores the metaphors and expressions employed by the monk-poet to describe the extremity of the ontological distance between the Creator and creatures. The acknowledgment of the extreme ontological distance, rather than leading to existential despair, can become a source of joy and gratitude when viewed through faith. The paper identifies some influences of early Eastern monastic spiritual traditions that echoed in the contemporary Carthusian author’s writings.